THE EFFECT OF THE BLOOD PRESSURE FEEDBACK INTERVENTION TO PHYSICIANS ON THE IMPROVEMENT OF THE BLOOD PRESSURE CONTROL - Rita Suhadi (Indonesian Journal of Pharmacy, 2014)
The study aimed to assess the effect of the blood pressure (BP) feedback intervention to physicians on the improvement of the blood pressure control of hypertension subjects. The study was done with controlled repeated intervention design. The adult hypertensive non-hemodialysis subjects from 4 Indonesian hospitals were included as intervention and control subjects. Outcomes were measured as the improvement of systolic BP (SBP). The subjects in intervention (n=385) vs. non-intervention (n=271) groups had similar age and proportion of males (p>0.05); proportion of cardiovascular comorbid 78.7% vs. 91.5% (p<0.01) and the baseline SBP at 144.1±15.8 vs. 139.6±13.8mmHg (p<0.01). The final SBP 138.2±17.2 vs.140.6±15.4mmHg (adjusted p<0.01); the difference between (∆) final-baseline SBP: 5.9±20.3 vs. (-)0.9±20.0mmHg (adjusted p<0.01); ∆final-target SBP: (-)6.1±17.3 vs.                     (-)9.6±15.5 (adjusted p<0.01). There were more intervention subjects with good controlled final SBP; odds ratio (OR) 1.4(CI95%:1.0-1.9, adjusted p<0.05). Based on the ∆final-baseline SBP, the ∆final-target SBP, and OR SBP reached the target; theintervention subjects had significant SBP improvement.